(untitled) (Marketing Journal, 2026)
This study examined advanced foreign experience in improving organizational and economic mechanisms for service sector development. Innovation support practices implemented in Japan, Germany, France, and CIS countries were analyzed. The impact of innovation infrastructure, technology transfer, commercialization of research outcomes, and private sector participation on development effectiveness was evaluated. Based on the findings, practical recommendations were developed to strengthen innovation activities, improve institutional mechanisms, and enhance competitiveness in the service sector. The results highlighted the importance of integrating international best practices into national development strategies.